‘A School Said to Resemble a Luxury Hotel’: Historicizing African Women's Quest for Education before Oprah's School - Charumbira, Ruramisai (History compass, 2009)
The public reception of the Oprah Winfrey Leadership Academy for Girls (OWLA) in South Africa and the United States is a recent example of a historical pattern historians have often called the ‘civilizing mission’ on behalf of girls and women in Africa. One of the greatest missed opportunities by founders (and critics) of such schools, past and the present, has been the glaring omission of highlighting contemporary African women's achievements so the girls can see themselves as connected to a long line of female strivers and achievers with varied personal histories. This study utilizes African women's novels and memoirs to historicize African women's quest for (higher) education as well as emphasize the importance of historically grounded international development aid to Africa so as to avoid the pitfalls of neocolonialism that reproduce stereotypes about Africans, and women in particular. Texts highlighted include: Tsitsi Dangarembga's Nervous Conditions, Mariama Bâ's So Long a Letter, Mamphela Ramphele's Across Boundaries, and Wangari Maathai's Unbowed.